Tailored and deep porosification of LTCC substrates with phosphoric acid. Issue 10 (August 2019) - Hajian, Ali; Smetaczek, Stefan; Zellner, Christopher; Stöger-Pollach, Michael; Konegger, Thomas; Limbeck, Andreas; Schmid, Ulrich
Abstract: Low temperature co-fired ceramics (LTCC) as an advanced technology for robust assembly of electronic components, has attracted significant attention in a wide application range such as in wireless communication or automotive radar systems. However, accurate designs of micromachined devices operated at high frequencies require substrates with regions of tailored permittivities. Introduction of controlled porosity into the substrate via wet-chemical etching procedure, is a promising approach for permittivity reduction which can be applied to commercially available LTCC without necessitating to alter their composition or sintering process. In the present study, by selective dissolution of celsian phase a very deep porosification (highest reported so far) could be realized while preserving the surface quality. Also, by a careful selection of the etching parameters, the depth of porosification and hence the permittivity reduction can be delicately tailored. Laser ablation inductively coupled plasma mass spectrometry was used for the investigation of chemical compositions of substrates.